Profil Pengolahan Tuna Loin Beku di PT. Harta Samudra Kabupaten Pulau Morotai - Titien Sofiati; Siti Nurbaya Deto (Politeknik Kelautan dan Perikanan Bitung, 2020)
The utilization of Tuna in Regency of Morotai Island include: selling the raw fish directly to consumers and processes to be a product. One of the refined products of Tuna that have come to international market is frozen Loin Tuna production from PT. Harta Samudra. The purpose of this research is to explain the Processing Profile of Frozen Loin Tuna at PT. Harta Samudra. This reseach be expected can give the information of the utilization of frozen Loin Tuna and become a the data base for advanced researches about frozen Loin Tuna at PT. Harta Samudra. The research take a place at PT. Harta Samudra on 7-14 Oktober 2019. The collecting data on field used survey method and semi-structural interview. The result of this research is the Processing of frozen Loin Tuna at PT. Harta Samudra consisted of: the accepted of staples, cleaning I, preparation and loin production, dark flesh disposal, barking, weighing, cleaning II, clear smoke injection, refigation, ozone spraying and retouching, final check, vacuum, refrigeration ABF, metal detector, packing and labeling, frozen storage, and stuffing. Keywords: Frozen Loin Tuna, Processing, PT. Harta Samudra